Determinants of Big Data Adoption for Higher Education Institutions in Malaysia - Tasmin, Rosmaini; Lay Huey, Tan (Research in Management of Technology and Business, 2020)
Big Data enables higher educational institutions the ability to efficiently use the information technology resources to enhance the effectiveness of education and performance. This research explores the characteristics of big data applicable to educational institutions, identifies the factors that affect the adoption of big data approach in higher education institutions, especially for strategic management purposes and aims to examine the challenges of adopting big data in higher education institutions. The literature references sources are from journals on scientific studies and articles, plus research papers. To achieve all of the objectives, the researcher uses qualitative research methodology for interviewing and analyzing the data from fifteen identified organisations, including authority, consulting firm, public and private universities. This research is expected to conclude the most important determinants, which is evincing the fact that big data management is essential for providing higher education institutions with enhance educational quality and to guide students, colleges and universities to better experience.